The Future of the Social Investment State 2020
DOI: 10.4324/9780429454752-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro-elderly welfare states within child-oriented societies

Abstract: Households and policies are the main vehicles of intergenerational transfers. Working-age people are net contributors; children and older persons net beneficiaries. However, there is an asymmetry in socialization. Working-age people pay taxes and social security contributions to institutionalize care for older persons as a generation, but invest private resources to raise their own children, often with large social returns. This results in asymmetric statistical visibility. Elderly transfers are near-fully obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Moreover, in line with the analysis of Bruno, Marelli, and Signorelli (), our results suggest that youth labor market indicators are less responsive to variation in compensatory spending as the total effects of a shock in these policy variables do not ultimately lead to an increased participation of the youth in the labor market. These results also highlight the importance of explicitly considering the role of intrafamilial transfers in future analysis as social investments may have a differential impact across childhood and early youth through family investments (Gál, Vanhuysse, and Vargha , Francesconi and Heckman ). At the same time, we need to be cautious as we did not consider any redistributive/differential effect that such policies can have at the individual levels (Bonoli and Liechti ; Pavolini and Van Lancker ), nor any regional spillover effects that policies can have among regions.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, in line with the analysis of Bruno, Marelli, and Signorelli (), our results suggest that youth labor market indicators are less responsive to variation in compensatory spending as the total effects of a shock in these policy variables do not ultimately lead to an increased participation of the youth in the labor market. These results also highlight the importance of explicitly considering the role of intrafamilial transfers in future analysis as social investments may have a differential impact across childhood and early youth through family investments (Gál, Vanhuysse, and Vargha , Francesconi and Heckman ). At the same time, we need to be cautious as we did not consider any redistributive/differential effect that such policies can have at the individual levels (Bonoli and Liechti ; Pavolini and Van Lancker ), nor any regional spillover effects that policies can have among regions.…”
Section: Discussionmentioning
confidence: 88%
“…This result is in line with the analysis of Bruno, Marelli, and Signorelli () who found that both NEETs and unemployment rates respond slowly to an increase in GDP, with many years elapsing before the situation of the young improves. In addition, as recent studies on intrafamilial transfers suggest (Gál, Vanhuysse, and Vargha , Francesconi and Heckman ), there is a danger in looking at data on public transfer alone without considering intergenerational transfers (cash) and the household economy (time), as social investments may have a differential impact across childhood and early youth through family investments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of socialisation of childcare will be equally important in a world with a rapidly shrinking population and where negative global population growth has a negative impact on the well-being of the population. In a scenario where population growth is a positive externality, a society might wish to instead increase the extent of socialisation of childbearing for the benefit of future generations (for example, Gál, Vanhuysse, & Vargha, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Welfare state societies specifically solve it through the inter-age-group resource transfers of the piggy bank in cross-section: surplus resources are taxed away from the working-aged to finance childhood and old age. European welfare societies engage in a division of labor to solve the problem: they are elderly-oriented welfare states relying on strongly child-oriented families [ 67 69 ]. Our general result obtains everywhere, even though there are country-specific differences within Europe as can be expected.…”
Section: Conclusion and Wider Implications: How We Evaluate Social Policiesmentioning
confidence: 99%